Fast and efficient extract oseltamivir from aquatic products using magnetic covalent organic frameworks/graphene oxide composite prior to liquid chromatography-tandem mass spectrometry analysis. (1st December 2022) - Shen, Rujia; Xu, Xuejiao; Shuai, Qin; Huang, Lijin
Highlights: Magnetic covalent organic framework/grapheme oxide (MCOF/GO) was prepared. MCOF/GO was effective for the extraction of oseltamivir. The established method was adopted to analyze oseltamivir in fish. The proposed method provided satisfactory linearity and limit of detection. Abstract: In this work, a magnetic covalent organic framework/graphene oxide composite (MCOF/GO) was rapidly synthesized and developed as a promising candidate for the magnetic solid-phase extraction (MSPE). Combined with HPLC-MS, an efficient and rapid analytical method was established for the determination of oseltamivir (OS) in aquatic products. The resultant composite not only exhibited superior extraction efficiency, but also possessed fast mass transfer kinetic, reducing the pretreatment time greatly. Under optimal conditions, the linear range of the proposed method for OS determination was found to be 0.1–10 μg/kg along with a satisfactory correlation coefficient (R 2 = 0.997) and a low limit of detection (LOD, 0.035 μg/kg). Furthermore, the established method was utilized to determine OS in Carp, Yellow croaker, and Shrimp, where the recoveries ranged from 87% to 116%. These results demonstrate the splendid application potential of this method to detect antiviral drugs in actual aquatic products.